PENGGUNAAN GADGET DENGAN KEJADIAN TEMPER TANTRUM PADA ANAK USIA 4-6 TAHUN - Yustanta, Brivian Florentis (STIKES dan AKZI Karya Husada Kediri, 2024)
Gadget is one of the sophisticated tools that provide various application features so that many parents give gadgets to children as a medium of learning, communication tools, and play. However, this condition makes parents begin to complain about changes in children's behavior such as crying, tantrums, and violent behavior if they are not given gadgets according to their wishes. This study aims to determine the relationship between gadget use and the incidence of temper tantrums in children aged 4-6 years at RA Plus Kartini Pakisrejo Tulunggaung. The research design is a retrospective cohort with a quantitative correlation approach. The independent variable in this study is the use of gadgets and the dependent variable is the incidence of temper tantrums. The population was 180 parents and a sample of 124 respondents with simple random sampling technique. The results showed that there was a significant relationship between the use of gadgets and the incidence of temper tantrums in children aged 4-6 years with a p value of = 0.007 < α = 0.05 so that H1 was accepted, meaning that there was a relationship between the use of gadgets and the incidence of temper tantrums.